A lower limb rehabilitation platform with mirror therapy, electrical stimulation and virtual reality for people with limited dorsiflexion movement. (April 2022) - Rosero-Herrera, J.D.; Acuña-Bravo, W.
Graphical abstract: Abstract: This paper presents a low-cost portable system for applying a rehabilitation therapy, based on virtual reality, functional electrical stimulation and a training device. This open-hardware system, intended to support a home-made therapy process in people with reduced dorsiflexion ability, contains three main building blocks: an electromechanical platform, an immersive virtual reality interface and the firmware. The electromechanical training platform is the core of the system, which acts as a gateway interface of sensors-actuators for a closed loop system, through an immersive virtual reality application, the patient closes the loop by acting as the controller by means of a "virtual dummy" preforming in mirror configuration. The platform measures and process the dorsiflexion angle described by both ankles, real-time transmitting the information to the mobile phone virtual application to be presented as a mirror. The onboard microprocessor drives the operation of the electric stimulation interface, which is sent through two channels to both, healthy and affected lower limbs. The platform communicates continuously through a USB bidirectional interface with a personal computer, in which the physician enters the rehabilitation protocol and follows the patient performance. A first case study by using this device has been reported in [1] .